Mental Capacity and Its Relationship to Cognitive Self-regulation among Middle School Teachers in the Dohuk Governorate Center - Dhaher, Shereen Khoder; Saeed, Sabir Abdullah; Muhammed, Muhammed Saeed (Journal of Tikrit University for Humanities, 2024)
The current research aims to know the level of mental capacity, the level of cognitive self-organization, and the significance of the differences in the level of mental capacity and cognitive self-organization among middle school teachers in the schools of the Dohuk Governorate Centerin order to achieve these goals, the researchers adopted the mental capacity test prepared by Pascal Leon (1970). It consists of (38) geometric shapes, and constructs a scale for cognitive self-regulation, which consists of (43) items with five alternatives: (always, often, sometimes rarely, never), After the test and scale were ready in final form and had appropriate psychometric properties, it was applied to a sample consisting of (850) middle school teachers in the (450) for extracting the results of the study. To treat the data statistically and extract the results, the following statistical methods were used (Pearson’s correlation coefficient, t-test for one sample). The study reached the following results there is a higher than average level of mental capacity among middle school teachers in the center of Dohuk Governorate. There is a higher than average level of cognitive self-regulation among intermediate school teachers in the center of Dohuk Governorate. There is a significant correlation between mental capacity and cognitive self-organization, and in light of the research results, the researchers reached a number of conclusions, recommendations, and proposals necessary for the parties related to the subject of the study.